Anticancer drug impact on DNA – a study by neutron spectroscopy coupled with synchrotron-based FTIR and EXAFS. Issue 8 (18th January 2019) - Batista de Carvalho, Ana L. M.; Mamede, Adriana P.; Dopplapudi, Asha; Garcia Sakai, Victoria; Doherty, James; Frogley, Mark; Cinque, Gianfelice; Gardner, Peter; Gianolio, Diego; Batista de Carvalho, Luís A. E.; Marques, M. Paula M.
Abstract : Complementary information on drug–DNA interplay has been achieved for Pt/Pd anticancer agents, by a combined QENS, SR-FTIR-ATR and EXAFS approach. Abstract : Complementary structural and dynamical information on drug–DNA interplay has been achieved at a molecular level, for Pt/Pd-drugs, allowing a better understanding of their pharmacodynamic profile which is crucial for the development of improved chemotherapeutic agents. The interaction of two cisplatin-like dinuclear Pt(ii ) and Pd(ii ) complexes with DNA was studied through a multidisciplinary experimental approach, using quasi-elastic neutron scattering (QENS) techniques coupled with synchrotron-based extended X-ray absorption fine structure (SR-EXAFS) and Fourier-Transform Infrared Spectroscopy-Attenuated Total Reflectance (SR-FTIR-ATR). DNA extracted from drug-exposed human triple negative breast cancer cells (MDA-MB-231) was used, with a view to evaluate the effect of the unconventional antineoplastic agents on this low prognosis type of cancer. The drug impact on DNA's dynamical profile, via its hydration layer, was provided by QENS, a drug-triggered enhanced mobility having been revealed. Additionally, an onset of anharmonicity was detected for dehydrated DNA, at room temperature. Far- and mid-infrared measurements allowed the first simultaneous detection of the drugs and their primary pharmacological target, as well as the drug-prompted changes in DNA's conformation that mediate cytotoxicity. The local environment of the absorbing Pd(ii ) and Pt(ii ) centers in the drugs' adducts with adenine, guanine and glutathione was attained by EXAFS.